2006
DOI: 10.1111/j.1471-4159.2006.04241.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and adult neurogenesis

Abstract: Dopamine is an important neurotransmitter implicated in the regulation of mood, motivation and movement. We have reviewed here recent data suggesting that dopamine, in addition to being a neurotransmitter, also plays a role in the regulation of endogenous neurogenesis in the adult mammalian brain. In addition, we approach a highly controversial question: can the adult human brain use neurogenesis to replace the dopaminergic neurones in the substantia nigra that are lost in Parkinson's disease?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 64 publications
7
141
1
5
Order By: Relevance
“…However, our FluoroGold tracing experiments unequivocally demonstrate that the cellcycle-like processes observed in vivo occurred in neurons that were already present before their intoxication. Thus, in agreement with other studies (15,23,24), we found no evidence for spontaneous or lesion-induced, transient or persistent, generation of new TH ϩ neurons in the adult SNc.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, our FluoroGold tracing experiments unequivocally demonstrate that the cellcycle-like processes observed in vivo occurred in neurons that were already present before their intoxication. Thus, in agreement with other studies (15,23,24), we found no evidence for spontaneous or lesion-induced, transient or persistent, generation of new TH ϩ neurons in the adult SNc.…”
Section: Discussionsupporting
confidence: 81%
“…Together, the available data suggest that cell cycle-associated mechanisms are linked to the process of neurodegeneration in PD. However, there have also been reports suggesting constitutive and lesioninduced neurogenesis in the adult SNc (15). Therefore, the observed cell-cycle events could be related to de novo generation of DNs as well.…”
mentioning
confidence: 97%
“…This adds to a list of studies that are revealing unexpected effects of neurotransmitters on neural stem/progenitor cell function. Apart from the work on the glutamatergic NMDA receptor subtype (Cameron et al, 1995;Gould and Cameron, 1997;Nacher and Mcewen, 2006), the dopaminergic impact on stem/progenitor cell proliferation during brain development and in adult neurogenesis has also been examined (Borta and Hoglinger, 2007;Hoglinger et al, 2004;Kippin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We found that cell proliferation in the hippocampal dentate gyrus was significantly increased following hypoxic ischemia, indicating that hypoxic ischemia induces cell proliferation in the hippocampal dentate gyrus. Hypoxic ischemia-induced enhancement of cell proliferation in the dentate gyrus has been suggested as a compensatory adaptive response to excessive apoptosis following ischemic brain injury (Liu et al 1998;Ko et al 2009) through alteration of dopaminergic inputs from the SN neurons (Borta and Höglinger 2007).…”
Section: Discussionmentioning
confidence: 99%